A Deep Blue Strong Microcavity Organic Light‐Emitting Diode Optimized by a Low Absorption Semitransparent Cathode and a Narrow Bandwidth Emitter - Seong Keun Kim; Mi Jin Park; Ramchandra Pode; Jang Hyuk Kwon (Advanced Photonics Research, 2021)
Herein, deep blue strong microcavity top‐emitting organic light‐emitting diodes (TEOLEDs) optimized by a low absorbed silver cathode and a narrow bandwidth emitter are reported for realizing high‐efficiency and narrow spectral characteristics. Usually, the Mg:Ag cathode is widely used as a semitransparent cathode in TEOLED devices due to its favorable reflectivity and proper electron injection ability. However, the high extinction coefficient of Mg causes a decrease in the microcavity effect, causing a low optical efficiency of devices. A Ag cathode is applied as a semitransparent cathode to modify the high absorption property for a strong microcavity blue OLED. At optimal conditions, the optically calculated device efficiency of TEOLEDs using a BPPyA emitter is 70.2 and 91.1 cd (A * y)−1 for Mg:Ag and Ag TEOLEDs, respectively. To further improve the device efficiency, an alternative emitter (DABNA‐NP‐TB) is applied which has a narrow bandwidth of 25 nm. The optically calculated efficiency enhancement in the TEOLED is about 23% compared with a control emitter, which is well correlated with the result of fabricated TEOLEDs.